Eclampsia as the leading cause of maternal death at Prof. dr. R.D. Kandou Hospital, Manado, Indonesia - Tendean, Hermie Meety Maasje; Sondakh, Joice Margaretha Mathilda; Lumentut, Anastasia Mariane; Ibrahim, Reni Christiani (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. One indicator of progress in a country's health is maternal mortality rate. 2. The characteristics of maternal mortality were examined in a regional hospital in North Sulawesi, Indonesia 3. Eclampsia was found to provide the most contribution to maternal mortality cases in the hospital. ABSTRACT Objectives: To determine the characteristics of maternal deaths at Prof. dr. R.D. Kandou Hospital, Manado, Indonesia, from January 1 to December 31, 2019. Materials and Methods: This was a retrospective descriptive study. Data were taken from the patient's medical record at Prof. dr. R.D. Kandou Hospital, Manado, in the period of January 1, to December 31, 2019. Results: From January 1 to December 31, 2019 in Prof. dr. R.D. Kandou Hospital, Manado, there were1.215 single live births, with maternal mortality of 22 cases. In the distribution of characteristics based on age, most patients had age range of 20-34 years with a total of 15 patients (68.18%) and parity 2 - 4 with a total of 21 patients (95,45%), Antenatal Care (ANC) of 1 – 3 times visit in a total of 11 cases (50%), and most came from outside the city of Manado with a total of 12 patients (54.54%). The most common cause of maternal death was due to eclampsia, comprising 8 cases (36.36%). Conclusion: Maternal death cases in Obstetrics and Gynecology Department of Prof. dr. R.D. Kandou Hospital, Manado, Indonesia, in 2019 reached 22 cases per 1.215 live births. Eclampsia was still the leading cause of maternal death.